Economic theory of bank credit - Hahn, L. Albert 1889-1968; Matt, Clemens; Hagemann, Harald (Oxford Oxford University Press, 2015)
L. Albert Hahn published the first edition of the 'Economic Theory of Bank Credit' in 1920 and a radically revised third edition in 1930. 'Economic Theory of Bank Credit' is a clear exposition of a theory of credit and stands in the tradition of Harley Withers, Henry Macleod, and Knut Wicksell. A theory of credit recognizes that banks are not only intermediaries of savings but in fact create money themselves. This idea is paired with a detailed account of the technical processes of the banking sector. In Part Two, Hahn provides an economic account of the effects of credit creation on the economy: banks vary their credit creation activity for various reasons and cause fluctuations in overall economic activity. Hahn therefore develops a monetary theory of the business cycle in the spirit of Schumpeter. The first and third editions draw different conclusions about central bank policy. The first edition is optimistic that an ever-lasting boom could be achieved, whilst the third edition sees the core function of central bank policy as smoothing economic fluctuations.0Translated by Matthew Clemens.
Includes bibliographical references and index.
Keywords: Credit; Banks and banking